EFFECTIVENESS OF EMPLOYEES PERFORMANCE AT YOUTH AND EDUCATION EDUCATION DEPARTMENT OF TAKALAR DISTRICT - Mannayong, Jumalia; Djafar, Raimurti (Jurnal Administrasi Negara, 2018)
Abstract The problem discussed in this research is low effectiveness of employee performance in youth education and sport agency of Takalar district. Based on this problem, this study aims to determine the effectiveness of employee performance in youth education and sport agency of Takalar district. The research method is descriptive qualitative. The type of data used in this research is secondary data. In order to obtain objective scientific results, the data is collected by obtaining initial data (raw data) directly and concluding it. is Instrument to gather the data are interviews, observation and document review. The results showed that the effectiveness of employee performance in youth education and sport agency of Takalar district by researching based on the indicators of the work quality, timeline, initiative, work competence and ability to communicate with other stakeholders have been declared effective. Constraints faced such as lack of ability of employees in the mastery of foreign languages and the assignation of employees who are not in accordance with their competence so far can be overcomed by the youth education and sport agency of Takalar district and does not affect the performance of employees